Circulating cell free DNA and miRNA Amount in Congenital Hearing Loss: Cell free DNA and miRNA in Congenital Hearing Loss - Caglar, Ozge; Cayir, Akin; Cilgin, Begum; Derekoy, Sefa (Acta Medica, 2018)
Objective: Our aim is to detect the amount of miRNA and free DNA in the peripheral blood of young people with congenital hearing loss and compare this with control group. Materials and Methods: In our study, 16 patients who have congenital hearing loss and go to the private school for deaf children and 16 healthy individuals were selected in the same age group. 5 cc blood was taken from peripheral vessels of each individual. We compared the circulating cell-free DNA and miRNA amount with the results of the control group. Results: The ccfDNA amount of the patients with hearing loss was lower than the control group and It was statistically significant. On the contrary, we found the higher amount of ccfmiRNA in plasma samples of the patients with hearing loss. The statistical analysis showed that ccfmiRNA amount in congenital loss is consistently significantly higher than the control group. Conclusion: The miRNA and freeDNA can be used early in the diagnosis of congenital hearing loss.